Shedding Light on the Origin of Solid‐State Luminescence Enhancement in Butterfly Molecules. Issue 61 (30th September 2020) - Sánchez‐Ruiz, Antonio; Rodríguez‐López, Julián; Garzón‐Ruiz, Andrés; Jiménez‐Pulido, Sonia B.; Illán‐Cabeza, Nuria A.; Navarro, Amparo; García‐Martínez, Joaquín C.
Abstract: Different molecular strategies have been carefully evaluated to produce solid‐state luminescence enhancement (SLE) in compounds that show dark states in solution. A set of α‐phenylstyrylarene derivatives with a butterfly shape have been designed and synthesised, for the first time, with the aim of improving the solid‐state fluorescence emission of their parent styrylarene compounds. Although these butterfly molecules are not fluorescent in solution, one of them (1, 2, 4, 5‐tetra(α‐phenylstyryl)benzene) exhibits a fluorescence quantum yield as high as 68 % in a drop‐cast sample and 31 % in its crystalline form. In contrast, 1, 3, 5‐tris(α‐phenylstyryl)benzene and 4, 6‐bis(α‐phenylstyryl)pyrimidine do not show SLE. A range of fluorescence spectroscopy experiments and DFT calculations were carried out to unravel the origin of different photophysical behaviour of these compounds in the solid state. The results indicate that a rational strategy to control the SLE effect in luminogens depends on a delicate balance between molecular properties and inter‐/intramolecular interactions in the solid state. Abstract : Shaped to soar : A new set of butterfly‐shaped α‐phenylstyrylarene derivatives are synthesised with the aim of improving the solid‐state fluorescence emission of their parent styrylarene compounds. X‐ray diffraction, fluorescence spectroscopy and DFT calculations are carried out to unravel the origin of different photophysical behaviours of these compounds in the solid state.